2013
DOI: 10.3109/07853890.2013.857831
|View full text |Cite
|
Sign up to set email alerts
|

Invasive and non-invasive techniques for detecting portal hypertension and predicting variceal bleeding in cirrhosis: A review

Abstract: Portal hypertension is a severe syndrome that may derive from pre-sinusoidal, sinusoidal and post-sinusoidal causes. As a consequence, several complications (i.e., ascites, oesophageal varices) may develop. In sinusoidal portal hypertension, hepatic venous pressure gradient (HVPG) is a reliable method for defining the grade of portal pressure, establishing the effectiveness of the treatment and predicting the occurrence of complications; however, some questions exist regarding its ability to discriminate bleed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 102 publications
0
22
0
Order By: Relevance
“…Furthermore, the American Association for the Study of Liver Diseases recommends that all liver transplant candidates must undergo transthoracic echocardiography. Since, cardiac dysfunction in cirrhosis seems not to be associated with the severity of liver disease [27], both an accurate patient selection for liver transplant [28,29] and a precise investigation for cirrhotic cardiomyopathy are mandatory. Indeed, cirrhotic cardiomyopathy may influence the outcome after liver transplantation [30][31][32]; moreover, liver transplantation may be responsible for additional intra-and postoperative short-and long-term cardiac morbidity [33].…”
Section: Pre-transplant Investigative Methodsmentioning
confidence: 99%
“…Furthermore, the American Association for the Study of Liver Diseases recommends that all liver transplant candidates must undergo transthoracic echocardiography. Since, cardiac dysfunction in cirrhosis seems not to be associated with the severity of liver disease [27], both an accurate patient selection for liver transplant [28,29] and a precise investigation for cirrhotic cardiomyopathy are mandatory. Indeed, cirrhotic cardiomyopathy may influence the outcome after liver transplantation [30][31][32]; moreover, liver transplantation may be responsible for additional intra-and postoperative short-and long-term cardiac morbidity [33].…”
Section: Pre-transplant Investigative Methodsmentioning
confidence: 99%
“…Previous studies reported a consistent relation between the splenic size and the portal venous pressure. This could be due to increased splenic red pulp blood volume from blood congestion in cirrhotic patients [1][2][3][4]. Other studies added that the most common parameters associated with varices include low platelet count, high prothrombin time, and increase in the Child-Pugh score.…”
Section: Discussionmentioning
confidence: 93%
“…Ultrasound transient elastography [10][11][12] and magnetic resonance elastography [13] are used to measure liver stiffness and predict esophageal varices but their results are preliminary and overlapping [10][11][12][13]. Endoscopy detects and grades the esophageal varices, Abdominal Imaging but it is an invasive procedure and is not accepted by many patients [1][2][3]. The hepatic vein pressure gradient is considered to be the gold standard for diagnosis of portal hypertension and esophageal varices in cirrhotic patients, but this is an invasive and expensive procedure that may be associated with potential complications [3,14].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Both of these modalities have been investigated whether measurements of portal parameters (eg. flow velocity or volume rate) may correlate with the degree of portal hypertension with variable results …”
mentioning
confidence: 99%